Clinical and electrophysiological examination of pinch strength in patients with amyotrophic lateral sclerosis. Issue 1 (9th November 2020) - Lee, John D.; Heshmat, Saman; Heggie, Susan; Thorpe, Kathryn A.; McCombe, Pamela A.; Henderson, Robert D.
Abstract: Background: The split‐hand concept has highlighted the preferential wasting of the thenar side of the hand in amyotrophic lateral sclerosis (ALS). Our objective is to re‐explore pinch grip strength to assess whether it has the potential to be a practical biomarker of ALS. Methods: We measured different pinch grip strengths (thumb, index, and fifth) using a pinch gauge from both hands of 54 ALS patients and correlated this with the Medical Research Council (MRC) score, the upper‐limb component of the revised ALS Functional Rating Scale – Revised (ALSFRS‐R) score, and compound muscle action potentials (CMAPs) that comprise the split‐hand index. Results: Pinch grip strength using any of the three fingers showed a positive correlation with its corresponding CMAP, MRC grading, and upper‐limb ALSFRS‐R score. The thumb pinch showed the strongest correlation with the split‐hand index and MRC grading. Conclusions: Pinch grip strength test using a simple gauge deserves further study as a potentially practical biomarker of ALS.